Neurodegeneration with inflammation is accompanied by accumulation of iron and ferritin in microglia and neurons - Maj Schneider Thomsen; Michelle Vandborg Andersen; Pia Rægaard Christoffersen; Malene Duedal Jensen; Jacek Lichota; Torben Moos (Neurobiology of Disease, 2015)
Chronic inflammation in the substantia nigra (SN) accompanies conditions with progressive neurodegeneration. This inflammatory process contributes to gradual iron deposition that may catalyze formation of free-radical mediated damage, hence exacerbating the neurodegeneration. This study examined proteins related to iron-storage (ferritin) and iron-export (ferroportin) (aka metal transporter protein 1, MTP1) in a model of neurodegeneration. Ibotenic acid injected stereotactically into the striatum leads to loss of GABAergic neurons projecting to SN pars reticulata (SNpr), which subsequently leads to excitotoxicity in the SNpr as neurons here become vulnerable to their additional glutamatergic projections from the subthalamic nucleus. This imbalance between glutamate and GABA eventually led to progressive shrinkage of the SNpr and neuronal loss. Neuronal cell death was accompanied by chronic inflammation as revealed by the presence of cells expressing ED1 and CD11b in the SNpr and the adjacent white matter mainly denoted by the crus cerebri. The SNpr also exhibited changes in iron metabolism seen as a marked accumulation of inflammatory cells containing ferric iron and ferritin with morphology corresponding to macrophages and microglia. Ferritin was detected in neurons of the lesioned SNpr in contrast to the non-injected side. Compared to non-injected rats, surviving neurons of the SNpr expressed ferroportin at unchanged level. Analyses of dissected SNpr using RT-qPCR showed a rise in ferritin-H and -L transcripts with increasing age but no change was observed in the lesioned side compared to the non-lesioned side, indicating that the increased expression of ferritin in the lesioned side occurred at the post-transcriptional level. Hepcidin transcripts were higher in the lesioned side in contrast to ferroportin mRNA that remained unaltered. The continuous entry of iron-containing inflammatory cells into the degenerating SNpr and their subsequent demise is probably responsible for iron donation in neurodegeneration. This is accompanied by only a slight increase in neuronal ferritin and not ferroportin, which suggests that the iron-containing debris of dying inflammatory cells and degenerating neurons gets scavenged by invading macrophages and activated microglia to prevent an increase in neuronal iron.